Three new species of Eurystethus from Brazil (Hemiptera: Heteroptera: Pentatomidae) - Correia, André Oliveira; Fernandes, José Antônio Marin; Campos, Luiz Alexandre (Zootaxa, 2021)
The Heteroptera (true bugs) and its fourth-largest family Pentatomidae (stink bugs) are worldwide distributed groups with higher diversity in the tropics. The pentatomid subfamily Discocephalinae is almost restricted to the Neotropical Region, and it is divided into the tribes Discocephalini and Ochlerini. Eurystethus Mayr, 1864 is placed within Discocephalini and comprises 18 species, 16 out of them classified into two subgenera. Here we describe Eurystethus jo sp. nov., Eurystethus multipunctatus sp. nov., and Eurystethus rufodorsatus sp. nov., all occurring in Brazil, compare them to other species and provide a distribution map.